DEFINING INDIA’S INTERNATIONAL OBLIGATIONS IN THE CONTEXT OF DOMESTIC LEGAL FRAMEWORK - Jain, Anshu; Kalgotra, Upasana (International Journal of Research -GRANTHAALAYAH, 2025)
India has consistently championed the cause of global peace and cooperation, committing itself to uphold international responsibilities for the betterment of humanity. The Indian Constitution includes provisions aimed at fulfilling these international obligations. This research paper will explore the influence of international treaties and conventions on the development and implementation of significant legislation within the Indian legal framework. The Constitution empowers Parliament to enact laws that give effect to international agreements and treaties, thereby promoting and respecting international law. The integration of international law through treaties is addressed in Articles 53, 73, 246, 253, and Entry 14 of List I in the Seventh Schedule of the Constitution. India has honored its commitments as a signatory to numerous treaties and conventions. Nevertheless, certain treaties necessitate specific legislation to address pressing issues such as the prevention of genocide and the protection of refugees.